Description of a new epibiotic relationship (Suctorian–Copepoda) in NE Atlantic waters: from morphological to phylogenetic analyses. (21st January 2015) - Gregori, Maria; Fernández‐Leborans, Gregorio; Roura, Álvaro; González, Ángel F.; Pascual, Santiago
Abstract: Paraeuchaeta hebes is one of the most important carnivorous copepods in the coastal upwelling system off Galician waters (Ría de Vigo, NE Atlantic). A suctorian epibiont of the genus Pelagacineta was found attached to the surface of these copepods. The abundance and distribution on the copepod surface were analysed, taking into account the sex of the crustacean, revealing some preference for females and also a different attachment point in both sexes. The morphological study allowed us to identify a new species of this Suctoria epibiont as Pelagacineta hebensis . Moreover, the 18S rRNA gene was partially sequenced to inspect the phylogenetic position of Pelagacineta hebensis within the subclass Phyllopharyngea. The maximum‐likelihood (ML) tree obtained was consistent with the morphological and with previous molecular studies and showed that P. hebensis belongs to the order Endogenina, as a sister clade of the few taxa sequenced within this order. Including new genetic data to the Endogenina will allow building new hypothesis about the evolution of the most derived clade of suctorians.